On Some Symmetric Systems of Difference Equations - Josef Diblík; Bratislav Iričanin; Stevo Stević; Zdeněk Šmarda (Abstract and Applied Analysis)
Here we show that the main results in the papers by Yalcinkaya (2008), Yalcinkaya and Cinar (2010), and Yalcinkaya, Cinar, and Simsek (2008), as well as a conjecture from the last mentioned paper, follow from a slight modification of a result by G. Papaschinopoulos and C. J. Schinas. We also give some generalizations of these results.